Toward Biological Pacing by Cellular Delivery of Hcn2/SkM1 - Végh, Anna M. D.; Verkerk, Arie O.; Cócera Ortega, Lucía; Wang, Jianan; Geerts, Dirk; Klerk, Mischa; Lodder, Kirsten; Nobel, Ruby; Tijsen, Anke J.; Devalla, Harsha D.; Christoffels, Vincent M.; Medina-Ramírez, Max; et al. (Frontiers in Physiology, 2021)
Electronic pacemakers still face major shortcomings that are largely intrinsic to their hardware-based design. Radical improvements can potentially be generated by gene or cell therapy-based biological pacemakers. Our previous work identified adenoviral gene transfer of Hcn2 and SkM1, encoding a ‘funny current’ and skeletal fast sodium current, respectively, as a potent combination to induce short-term biological pacing in dogs with atrioventricular block. To achieve long-term biological pacemaker activity, alternative delivery platforms need to be explored and optimized. The aim of the present study was therefore to investigate the functional delivery of Hcn2/SkM1 via human cardiomyocyte progenitor cells (CPCs). Nucleofection of Hcn2 and SkM1 in CPCs was optimized and gene transfer was determined for Hcn2 and SkM1 in vitro. The modified CPCs were analyzed using patch-clamp for validation and characterization of functional transgene expression. In addition, biophysical properties of Hcn2 and SkM1 were further investigated in lentivirally transduced CPCs by patch-clamp analysis. To compare both modification methods in vivo, CPCs were nucleofected or lentivirally transduced with GFP and injected in the left ventricle of male NOD-SCID mice. After one week, hearts were collected and analyzed for GFP expression and cell engraftment. Subsequent functional studies were carried out by computational modelling. Both nucleofection and lentiviral transduction of CPCs resulted in functional gene transfer of Hcn2 and SkM1 channels. However, lentiviral transduction was more efficient than nucleofection-mediated gene transfer and the virally transduced cells survived better in vivo. These data support future use of lentiviral transduction over nucleofection, concerning CPC-based cardiac gene delivery. Detailed patch-clamp studies revealed Hcn2 and Skm1 current kinetics within the range of previously reported values of other cell systems. Finally, computational modelling indicated that CPC-mediated delivery of Hcn2/SkM1 can generate stable pacemaker function in human ventricular myocytes. These modeling studies further illustrated that SkM1 plays an essential role in the final stage of diastolic depolarization, thereby enhancing biological pacemaker functioning delivered by Hcn2. Altogether these studies support further development of CPC-mediated delivery of Hcn2/SkM1 and functional testing in bradycardia models.